PENGARUH KEPEMIMPINAN, PENDIDIKAN DAN PELATIHAN, DAN PENGEMBANGAN KARIER TERHADAP KINERJA PEGAWAI DI BKKBN - Dwi Hartini; Ahmad Dirwan (Jurnal Ilmiah Manajemen SURYA PASCA SCIENTIA, 2023)
This research aims to obtain fact data, and valid and correct information, and can be trusted about the influence of Leadership, Education and Training, and Career Development on Employees Performance in the Main Secretariat of the National Population and Family Planning Board. This research is conducted by using quantitative research approach, by using survey method, including survey, consolidation, test instrument through validity and reliability test, and data collection and processing of research result. The sample of this study is the entire population is affordable, and has the same character, that is as many as 76 employees echelon IV for the sample of research, taken at random simple, qualified research. The measurements in this study were conducted by giving the value of each item in question of all variables, the size of the values given in each statement using "Likert Scale". Based on result of research analysis: 1) There is influence of Leadership (X1) to Career Development (X3) equal to 22,8% 2) There is influence of Education and Training (X2) to Career Development (X3) equal to 25,1% 3) There is influence of Leadership (X1) to Employees Performance (Y) equal to 32,6% 4) There is influence of Education and Training (X2) to Employees Performance (Y) equal to 10,7% 5) There is influence of Career Development (X3) to Employees Performance (Y) equal to 30,3%.Key Words: Leadership, Education and Training, Career Development, Employees Performance